Analysis of Multiple Characters of Major Character in the Novel Tell Me Your Dreams by Sydney Sheldon, as an Alternate Material to Teaching Prose - Ida Susanti (Universitas PGRI Semarang, 2017)
This research is purposed to analysis of multiple characters of major character in the novel Tell Me Your Dream by Sidney Sheldon. Like any other Sheldon’s previous novel, this novel tells an interesting mysterious story with a woman as the main character. Reading literature such as novels is interesting and challenging. It requires a different approach than reading a textbook.The writer can apply the knowledge about multiple character presented in the novel that can be used to convey informations.And the last but not least the writer can give contribution to teach prose.Based on background of the topic, writer states the exact problems of this study as follows: (1) What is multiple characters generally? (2) What are multiple characters of main character found in the novel? (3) What does Tell Me Your Dreamscontribute to Teaching Prose? Based on the problem the writer states, the objectives of this study as follows: (1) To explain the multiple characters definition.(2) To explain the multiple characters of main character found in the novel. (3) To explain what Tell Me Your Dreams novel contributes to Teaching Prose. This research uses data collection method with Content-analysis: A review of research in any area, for instance, involves the analysis of the contents of research articles that have been published. The technique of data analysis through some ways such as reading the novel, books and international journal, classifying the data, and analyzing the content of the novel.Based on the analysis, the writer concludes that Tell Me Your Dreams a novel written by Sidney Sheldon in 1998 is one of the media of teaching prose for example analyzing a novel. The contributions of analyzing novel for Teaching Proses are an alternative fun way of studying prose, increasing student interest in the preservation of literature and increasing students’ listening ability reading ability, writing ability, and speaking ability